THE SPRINGTAILS (INSECTA: COLLEMBOLA) FAUNA AT DIFFERENT MICROHABITATS OF BEČIĆI BEACH, MONTENEGRO - Jakšić, Tatjana R; Vasić, Predrag S; Labus, Nenad Đ; Papović, Olivera M; Stanojević, Miloš R; Đukić, Nikola N (Bulletin of Natural Sciences Research, 2017)
Collembola fauna has been investigated at different microhabitats near the beach in Bečići, Montenegro. Samples were collected from four locations: Hotel “Tara”, “Sveti Toma” Church (St. Thomas), Hotel “Naftagas” and “Zelena Stena” (Green Rock). Each of the location presented different microhabitat: under the palm tree, cypresses tree, larch tree and white pine tree. Samples were taken in May and September 2015 and results presented as qualitative findings. Total number of 30 Collembola species was identified, classified into six families and 17 genera. Representatives of the family Hypogastruridae and Isotomidae were recorded at all of the studied sites, while representatives of the families: Naenuridae, Onychiuridae, Entomobryidae and Sminthuridae were present on some of locations. The biggest number of species and the highest Collembola population density was found at the Green Stone site, 24 species in total, microhabitat- white pine, and the smallest number of species, 6 on site “St. Thomas” Church, microhabitat- cypresses trees.